2017
DOI: 10.1007/s11356-017-0529-6
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide influence on metal behavior in a polluted southern Mediterranean lagoon: implications for management

Abstract: The degree of pyritization and degree of trace metal pyritization (DTMP) were investigated in sediments from Ghar El Melh Lagoon (northern Tunisia) in order to study metal deposition. A sediment core and 28 samples were thus taken in summer 2008, and metals and sulfate were analyzed in pore water/pyrite. Acid-volatile sulfide and metals were simultaneously extracted from these two fractions and the role of pyrite in the metal cycling studied. To examine pyrite presence and mineralogical form in sediments, X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Additionally, the mean AVS/CRS ratios in JL and JH were 0.34 and 0.19, respectively; thus, efficient conversion of AVS to CRS could occur in JL and JH. The result was in agreement with a previous study, in which effective conversion of AVS to CRS occurred in sediments (Oueslati et al 2018).…”
Section: Sulfur-iron Sedimentation Under High Salinity and Heavy Pollutionsupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, the mean AVS/CRS ratios in JL and JH were 0.34 and 0.19, respectively; thus, efficient conversion of AVS to CRS could occur in JL and JH. The result was in agreement with a previous study, in which effective conversion of AVS to CRS occurred in sediments (Oueslati et al 2018).…”
Section: Sulfur-iron Sedimentation Under High Salinity and Heavy Pollutionsupporting
confidence: 93%
“…A previous study showed that Eq. 4 predominated when the pH was approximately 7 in sediments (Oueslati et al 2018). According to the pH values (5.4, Table S4), the formation of CRS in JL might be attributed to Eq.…”
Section: Sulfur-iron Sedimentation Under High Salinity and Heavy Pollutionmentioning
confidence: 91%
See 3 more Smart Citations